Viral Etiology of Acute Gastroenteritis Among Forcibly Displaced Myanmar Nationals and Adjacent Host Population in Bangladesh. (29th September 2021) - Hossian, Mohammad Enayet; Islam, Md Muzahidul; Miah, Mojnu; Haque, Warda; Vinjé, Jan; Rahman, Mohammed Ziaur; Faruque, Abu Syed Golam; Khan, Azharul Islam; Ahmed, Tahmeed; Rahman, Mustafizur
Abstract: Background: Since August 2017, Myanmar nationals from Rakhine state have crossed the border into Bangladesh and settled in Cox's Bazar, the World's largest refugee camp. Due to overcrowding, poor sanitation, and hygienic practices they have been under significant health risks including diarrheal diseases. The objective of this study is to determine the viral etiology of acute gastroenteritis (AGE) among forcibly displaced Myanmar nationals (FDMN) and adjacent Bangladeshi local host population (AHP). Methods: From April 2018 to April 2019, we collected stool specimens from 764 FDMN and 1159 AHP of all ages. We tested 100 randomly selected specimens from each group for the most common AGE viruses. Results: Among 200 diarrhea patients, 55% and 64% of FDMN and AHP patients, respectively, had viral infections; the most common viruses were rotavirus (29% vs 44%), adenovirus (24% vs 31%), and norovirus (14% vs 10%). In both populations, viral infections were significantly higher in children less than 5 years of age, compared with bacterial infections that were higher in patients older than 5 years of age ( P ≤ .05). Conclusions: Disparities in viral and bacterial prevalence among various age groups warrant careful antibiotic usage, especially in children less than 5 years of age.